Dos cartas inéditas de Cadalso como censor - Philip Deacon (Cuadernos de Ilustración y Romanticismo)
In 1979 Nigel Glendinning and Nicole Harrison published all the then known letters of José de Cadalso, including four relating to a request from the Printing Judiciary for him to act as censor. The present article reveals that the military writer was previously contacted by the same institution, in 1772, to censor a text by the lawyer Vicente Vizcaíno Pérez entitled Women's Complaints against Men, proposing a greater use of female labour in areas then dominated by men. The work was never published and its contents remain unclear. Because of its potential repercussions, Cadalso alleged his own lack of expertise suggesting that the text be assessed by experts in the various fields. The article attempts to set the text and details of the careers of Cadalso y Vizcaíno.